2023
DOI: 10.14569/ijacsa.2023.0140272
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prediction using Machine Learning Models

Abstract: Breast cancer is a type of cancer that develops in the cells of the breast. Treatment for breast cancer usually involves X-ray, chemotherapy, or a combination of both treatments. Detecting cancer at an early stage can save a person's life. Artificial intelligence (AI) plays a very important role in this area. Therefore, predicting breast cancer remains a very challenging issue for clinicians and researchers. This work aims to predict the probability of breast cancer in patients. Using machine learning (ML) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Their model outperformed the baselines. Another study handled the classification of disaster tweets by exploring bag-of-words and several ML models ( Iparraguirre-Villanueva et al, 2023 ). The highest performance achieved is 87% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Their model outperformed the baselines. Another study handled the classification of disaster tweets by exploring bag-of-words and several ML models ( Iparraguirre-Villanueva et al, 2023 ). The highest performance achieved is 87% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it is based on identifying the k nearest k data points within the training set, after that, it performs the prediction or classification of the data based on the majority class of the nearest neighbors [66]. To measure the distance between its neighbors, the model uses the Euclidean equation for continuous variables, as shown in (5), and for discrete variables, it uses the overlap metric [67], [68] The model is widely used in the prediction of some diseases such as type 2 diabetes or for movie recommendations [69], [70]. (5)…”
Section: K-nearest Neighborsmentioning
confidence: 99%
“…Results demonstrated not only children belonging to the experimental group enjoyed learning through AR, but teachers also found the AR designs to be attractive to make children learn.GeoGebra(a free Math Tool) [12] when integrated with AR provided a good learning experience and better performance to school students. This experimental method was carried out by IparraguirreVillanueva, Orlando, et al [29], where they studied 78 students and found that 70% of the experimental group had outstanding performance while the remaining 30% students could reach the expected level of learning. Considering the controlled group that were taught without AR integration 10% achieved expected level performance, 85% were progressing and 5% were still in their initial stage.…”
Section: Mathspace [25]mentioning
confidence: 99%